The psychopathological impact of the SARS-CoV-2 epidemic on subjects suffering from different mental disorders: An observational retrospective study. (January 2022) - Caldiroli, Alice; Capuzzi, Enrico; Tringali, Agnese; Tagliabue, Ilaria; Turco, Marco; Fortunato, Andrea; Sibilla, Matteo; Montana, Caterina; Maggioni, Laura; Pellicioli, Cristian; Marcatili, Matteo; Nava, Roberto; et al.
Highlights: COVID-19 pandemic differently affected the psychopathology of mental disoders. Personality disorders resulted to be particularly affected by lockdown measures. Psychotic and obsessive-compulsive symptoms did not improve when lockdown ended. Continuity of care is particularly important for psychotic and OCD patients. Targeted interventions should be considered in the different phases of the pandemic. Abstract: SARS-CoV-2 infection causes a pulmonary disease (COVID-19) which spread worldwide generating fear, anxiety, depression in the general population as well as among subjects affected by mental disorders. Little is known about which different psychopathological changes the pandemic caused among individuals affected by different psychiatric disorders, which represents the aim of the present study. Specific psychometric scales were administered at three time points: T0 as outbreak of pandemic, T1 as lockdown period, T2 as reopening. Descriptive analyses and linear regression models were performed. A total of 166 outpatients were included. Overall, psychometric scores showed a significant worsening at T1 with a mild improvement at T2. Only psychopathology in schizophrenia (SKZ) patients and obsessive-compulsive (OC) symptoms did not significantly improve at T2. Subjects affected by personality disorders (PDs) resulted to be more compromised in terms of general psychopathology than depressed and anxiety/OC ones, and showed more severe anxiety symptoms than SKZ patients. In conclusion, subjects affected by PDs require specific clinical attention during COVID-19 pandemic. Moreover, the worsening of SKZ and OC symptoms should be strictly monitored by clinicians, as these aspects did not improve with the end of lockdown measures. Further studies on larger samples are needed to confirm our results. ClinicalTrials.gov Identifier: NCT04694482